Functional outcome of complex acetabular fractures by combined anterior and posterior approach in a single sitting: a case report - Mahajan, Neetin P.; Sadar, Amey; Kondewar, Pranay; Hifzur, Syed Rahman; Shrivastava, Sushant; Kale, Ninad (International Journal of Research in Orthopaedics, 2022)
Complex acetabular fractures described by Judet and Letournel present with a formidable diagnostic and therapeutic challenge. Simultaneous anterior and posterior exposures of the acetabulum are a safe and are useful alternative to other extensile exposures and can be performed with similar morbidity. The advantages of simultaneous anterior and posterior approaches over extensile exposures include less morbidity, less hospital stay, early mobilisation and avoidance of soft tissue contracture. The combined approach is most useful in transverse, transverse posterior wall fractures with wide anterior displacement, T type fractures with significant anterior-inferior displacement, or both column fractures with posterior wall involvement. 23-year-old male came with chief complaints of pain and swelling at right hip since 3 days. He had history of fall from train and then referred to us for further management. clinical and radiological assessment was done. Approachment of the case was done with combined anterior and posterior incision in single sitting. It provided excellent clinical and radiological outcome. Complex acetabular fracture is a challenging entity. Association of these fractures with complex anatomy, delicate soft tissue handling and extensive blood loss makes it more difficult to manage. Combined anterior and posterior approaches of aceatabulum in a single sitting can be used as safe alternative to step wise extensible approaches used routinely. Outcomes associated with single sitting are good as its associated with lesser morbidity of patient, early functional mobility and less hospital stay. Though it’s not devoid of its own complications decision must be taken depending upon the condition of the patient and surgeon’s choice.